The effectiveness of debt review in terms of the National Credit Act 34 of 2005 as a debt relief measure for over-indebted consumers - Boraine, A. (Andre), 1957- (University of Pretoria, 2024)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2023.